Craniofacial Fibrous Dysplasia: Surgical Management and Long-Term Outcomes at a Referral Center in Mexico City - Lopez-Garibay, Luis Alejandro; Guevara-Valmaña, Osvaldo; Telich-Tarriba, Jose Eduardo; Navarro-Barquín, David Felipe; Haro-Alvarez, Natalia; Andrade-Delgado, Laura; Martínez-Wagner, Rogelio (Indian Journal of Plastic Surgery, 2023)
Background Craniofacial fibrous dysplasia (CFD) is an uncommon benign condition in which a bone is replaced by fibrous tissue. An adequate clinical characterization considering the number of affected bones and functional impairment is important to determine the most effective surgical intervention for its management. This study aims to present our institution's experience in the evaluation and management of CFD.Methods This was a retrospective study that included patients with CFD managed at our institution. Data included demographic characteristics, afflicted bones, surgical procedures performed, and recurrence. Results are presented as mean and percentages. Recurrence-free years and association between the type of surgery and recurrence was evaluated.Results Eighteen patients were included (11 females, 61%). The zygomatic, maxillary, and frontal bones were the most commonly affected with eight (18%) cases each. The most common procedure was bone burring, with 36 procedures. Recurrence was more prevalent after burring (58.3%) and occurred earlier than in the bone resection group (13 vs. 15 years, p > 0.05).Conclusion Surgery continues to be the cornerstone of CFD treatment. Bone burring is effective for debulking and contouring but increases the risk for recurrence. An individualized approach should be tailored according to the anatomical location of the disease, type of CFD, behavior of the lesion, and accompanying clinical complaints.
Keywords: fibrous dysplasia; polyostotic; craniofacial fibrous dysplasia; mandibular osteotomy; follow-up studies; recurrence; GTP-binding proteins